Instituciones de interés para la filosofía jurídica como fuentes de información - Villaseñor Rodríguez, Isabel (Revista General de Información y Documentación, 2009)
The text presents some of the institutions of greatest interest to users of the Documentation on Legal Philosophy as sources of information invaluable since the nineteenth century to today. There is more interest in the initial stage of the institutions surveyed.